Konsep dan Implementasi Kepemimpinan Pendidikan Efektif dalam Mewujudkan Sekolah Berprestasi - Zahra Lahitania; M. Imamul Muttaqin (Ikhlas : Jurnal Ilmiah Pendidikan Islam, 2025)
Educational leadership plays a crucial role in achieving high-performing schools, particularly in the context of the demand for holistic improvement in educational quality. Educational leadership acts as a catalyst in creating a conducive learning environment, directing school management effectively, and motivating all school stakeholders to achieve shared goals. This study aims to examine the concepts, fundamental principles, and implementation of effective educational leadership in managing high-performing schools. Additionally, this research analyzes the supporting and inhibiting factors in the application of educational leadership and proposes strategies to overcome the challenges encountered. The method employed is a literature review to gather relevant data and information. The findings indicate that effective educational leadership significantly contributes to enhancing teacher motivation and performance, fostering a positive school culture, and optimizing student achievement. These findings underscore the importance of active educational leadership in adopting innovative and adaptive strategies to create outstanding and competitive schools.